Exploring phenotypic and genetic diversity of natural Saccharomyces cerevisiae strains for improved recombinant cellulase secretion - Davison, Steffi Angela (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.